Uma irresistível vocação para cultivar a própria personalidade (Parte II) An irresistible tendency to cultivate one's own personality - Paulo Eduardo Arantes (Trans/Form/Ação, 2003)
Estudo da relação entre os judeus cultivados de Berlim (na figura de Rachel Varnhagen) e a cultura clássica alemã por meio da análise do papel nela representado pela idéia de "personalidade", senha da ideologia dos mandarins alemães. Study of the relationship between the cultivated jews of Berlin (represented by the figure of Rachel Varnhagen) and the German classical culture through the analysis of the role played in the latter by the idea of "personality", codeword of the German mandarins' ideology.